The relationship between the philosophy of Sejahtera and Maqasid Shariah - Ab Razak, Ratna Roshida; Zakaria, Muhammad Hafeez (The American Journal of Humanities and Social Sciences Research (THEAJHSSR), 2024)
Sejahtera, as a concept of living among Malaysians that is based on local wisdom, needs to be constantly strengthened to become a guide to ensure true happiness in life. This paper aims to explore the philosophy of Sejahtera, which is a concept of living among Malaysians that is derived from the wisdom of Islamic beliefs and how it is closely related to Maqasid Shariah. This effort is important to make the philosophy of Sejahtera applicable in various aspects of Malaysian life, such as education, as outlined in the National Education Philosophy. The philosophy of Sejahtera can be considered as spiritual health that results from a balance based on the three main components of human existence. These three components are also elements in the five objectives of Shariah or Islamic law, which are to safeguard religion, intellect, life, progeny, and property. Sejahtera, in this context, is the application of Malaysian societal values that are seen as an act of becoming a human being who loves oneself, God, others, and also the environment. This study uses a content analysis approach involving secondary data from literature reviews. The qualitative data collected were analysed descriptively. The study found that the philosophy of Sejahtera is a philosophy of life that is closely related to the objectives of Shariah or Islamic law through an emphasis on balance in all aspects of life.